Elaboração e aplicação de jogos como recurso didático na aprendizagem de química no ensino médio - Moreira, Adeirton Freire (2019)
In view of the numerous difficulties in the methodological processes of the Teaching of Chemistry, the need arises for the improvement of methods and instruments that aid in learning in the discipline of Chemistry. The purpose of this study was to elaborate, apply and investigate the use of games as a didactic resource in the learning of Chemistry in High School, detecting possible difficulties in learning and correcting them, in order to encourage the development of knowledge of Chemistry. To verify the efficiency of this work, three classes of Chemistry of High School, one of each grade, of a public school of the interior of the State of Ceará, were used as research field, through the use of six games (two for each grade), end of classes or closure of content or chapters. The work was based on a series of texts on games in the discipline of Chemistry, having as a foundation of teaching a Vygotskyan view, which approach the uses of such tools and the role of the teacher in this socio-pedagogical mechanism and that allow a greater harmony between the content and the student body. The methodology was centered on the application of games as a complement after the content exposition and application of activities, to analyze the possibilities of the efficiency of these games in the purpose of the cognitive evolution in the discipline. The data collected showed favorable results for the application of the games, indicated by the improvement of student grades, greater interaction, cooperation and softening of doubts arising in the resolution of activities, thus reaching the expectations stipulated in the objectives of this work. It is concluded that the didactic use of the games applied to Teaching Chemistry presented with great pedagogical potential for the search of the improvement of teaching and learning. At the end of this research was produced an Educational Product, in the form of a Guide to Instruction and Confection with the six games tested in this research, which allows to bring to other Chemistry teachers greater dynamism and diversification of their pedagogical practices.